PENGARUH INDEPENDENSI, PENGALAMAN, DUE PROFESSIONAL CARE, AKUNTABILITAS, KOMPLEKSITAS AUDIT, DAN TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT (Studi Empiris pada Auditor KAP di Jawa Tengah dan DIY) - Rr Putri Arsika Nirmala; Nur Cahyonowati (Diponegoro Journal of Accounting, 2013)
This research was aimed to analyze and provide empirical evidences about the impact of independency, experience, due professional care, accountability, audit complexity, and time budget pressure on audit quality. This study was conducted by using survey method with questionnaire. The population in this study are auditors who work in public accountant offices in Central Java and DIY. This study used convenience sampling which was conducted by determination of samples counted with Slovin formula, so that only 91 questionnaires could be processed. Data analysis was conducted using multiple regression model. The result proved that independency, experience, due professional care, accountability, audit complexity, and time budget pressure influenced audit quality simultaneously. Besides that, this study proved that independency, experience, due professional care, accountability, and time budget pressure influenced audit quality partially, but audit complexity didn’t influence audit quality.